The Role Of Maintenance Hormonal Therapy In High Grade Epithelial Ovarian Cancer (Journal of Pharmaceutical Negative Results, 2023)
Background: Epithelial ovarian cancer is the leading cause of death from gynecologic cancer in the United State and is the fifth most cause of cancer mortality in women. Primary treatment for presumed ovarian cancer consists of appropriate surgical staging and debulking surgery, followed in most (but not all) patients by systemic chemotherapy. Comprehensive surgical staging is the mainstay of diagnosis and initial treatment for ovarian, fallopian tube, and peritoneal cancers. After initial cytoreductive surgery and subsequent chemotherapy, management of EOC may include maintenance therapy. Targeted maintenance therapy is defined as the maintenance administration of a single-agent antibody or small-molecule inhibitor after the completion of chemotherapy. The rationale for maintenance therapy is to delay the disease from progressing by either eliminating residual slowly dying cancerous remnants, retarding cell turnover via inhibitory signaling, preventing tumor neo-angiogenesis, or through immunologic control. Hormonal treatment is commonly used as a treatment option in patients with recurrent ovarian cancer who have exhausted or are not suitable for further standard lines of systemic chemotherapy, also been postulated to be effective in the setting of relapsed disease with a rising CA125 before the onset of significant clinical symptoms. Hormonal therapy provides an attractive therapeutic option in these patients due to the convenience of oral administration, and generally tolerable safety profile compared to chemotherapy and other targeted therapies.